Assessing Economic Resilience of Wetland Villages as a Foundation for Rural Investment: An Index-Based Study in Bengkalis Regency, Indonesia - Taryono; Lapeti Sari; Rahmita Budiarti Ningsih; Khusnul Fikri; Lailan Tawila Berampu (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study analyzes the economic resilience of wetland villages as a basis for promoting rural investment in Siak Kecil Subdistrict, Bengkalis Regency, Indonesia. The study focuses on the importance of aligning rural investment strategies with local strengths and wetland ecosystem characteristics to support sustainable development. Design/methodology/approach – Economic resilience is measured using indicators such as production diversity, access to basic economic infrastructure, presence of local financial institutions, and regional accessibility. A scoring method (0–5) is applied, and the results are compiled into an Economic Resilience Index (ERI) ranging from 0 to 1. Findings/Results – Applying a 12-indicator ERI framework across 17 wetland villages, the findings reveal that production diversity is high and nearly uniform across villages, so that differences in overall resilience are driven mainly by credit access, market/retail infrastructure, and regional accessibility. Using a mean ± 0.5 SD classification rule, four villages (Lubuk Muda, ERI = 1.00; Sungai Nibung, 0.9167; Sungai Siput, 0.90; Sungai Linau, 0.8833) fall into the High resilience category, seven fall into the Medium category, and six villages (including Lubuk Garam, the lowest at 0.65) fall into the Low category, with credit facility access and public transportation identified as the main constraints separating lower- from higher-tier villages. Originality/Value – This study contributes a transparent, rule-based 12-indicator Economic Resilience Index (ERI) for Southeast Asian wetland village contexts, where village-level investment readiness remains undermeasured relative to social- or ecological-resilience approaches; full replicability and objectivity of the index depend on continued validation and reporting of the underlying scoring rules and raw indicator data. By combining IDM secondary data (2024) with field-verified primary data across all 17 villages of a wetland sub-district and applying a transparent, rule-based classification of resilience tiers, the study offers a planning foundation rather than a direct measurement of investment outcomes; improving infrastructure, strengthening local institutions, and expanding financing access are identified as the priority levers for inclusive and sustainable rural development in Riau's coastal wetland areas.